2017
DOI: 10.1111/jpm.12372
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric properties of the 5‐item gratitude questionnaire in Chinese adolescents

Abstract: Background This study was conducted to evaluate the psychometric properties of the Chinese version of the 5-item Gratitude Questionnaire (GQ-5). Method The sample consisted of 2093 middle school students (46.8% males) in mainland China. Confirmatory factor analysis and multigroup confirmatory factor analysis were performed to examine the factor structure and the measurement equivalence across gender. The convergent validity, Cronbach's α and mean interitem correlations of the GQ-5 were also evaluated. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
11
19
0
1
Order By: Relevance
“…The results of the current study indicated that the one-factor with five items model of the GQ possessed a more satisfactory factor validity than the six-item model. The five-item solution was consistent with other GQ validations with university students from different countries (Chen et al, 2009; Langer et al, 2016; Yüksel & Oğuz, 2012; Zeng et al, 2017). In addition, a previous study conducted in Spain comparing the two models of the GQ by means of CFA showed that the 5-item approach was the most parsimonious (Bernabé-Valero et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of the current study indicated that the one-factor with five items model of the GQ possessed a more satisfactory factor validity than the six-item model. The five-item solution was consistent with other GQ validations with university students from different countries (Chen et al, 2009; Langer et al, 2016; Yüksel & Oğuz, 2012; Zeng et al, 2017). In addition, a previous study conducted in Spain comparing the two models of the GQ by means of CFA showed that the 5-item approach was the most parsimonious (Bernabé-Valero et al, 2013).…”
Section: Discussionsupporting
confidence: 85%
“…Fourthly, the reliability of the GQ was appropriate given Cronbach’s alphas and CR found. In addition, the five-item GQ presented a similar reliability to those reported in other validation studies, with Cronbach’s alphas between .70 and .80 (Chen et al, 2009; Langer et al, 2016; Yüksel, & Oğuz, 2012; Zeng et al, 2017).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, studies exploring the differences in reactive aggression are also inconclusive, with some research reporting that male reactive aggression was higher than female [ 81 , 82 ], while no gender differences were observed in others [ 18 , 83 , 84 ]. Moreover, studies suggest that females seek less revenge [ 34 , 85 , 86 ] and are more grateful than males [ 87 , 88 , 89 , 90 , 91 ]. The literature has also found differences by age.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research was also conducted that assessed the linkage of gratitude to academic outcomes especially in non-Western and collectivist settings (i.e., Philippines). Previous studies primarily focused on GQ-6’s factor structure and its association with well-being outcomes (i.e., mainland Chinese, Taiwanese, and Filipino samples; Chen, Chen, Kee, & Tsai, 2009; Chen & Kee, 2008; Datu, 2014; Datu & Mateo, 2015; Zeng, Ling, Huebner, He, & Lei, 2017).…”
mentioning
confidence: 99%